ChemInform Abstract: Reductive Iodonio‐Claisen Rearrangement of Iodothiophene Diacetates with Allylsilanes: Formal Synthesis of Plavix®. Issue 4 (28th January 2014) - Nguyen, Hai; Khatri, Hem Raj; Zhu, Jianglong
Abstract Iodothiophene diacetates react with allyltrimethylsilanes in the presence of boron trifluoride diethyl etherate to afford the corresponding ortho‐allyliodothiophenes via a reductive iodonio‐Claisen rearrangement.